Carboxymethyl cellulose assisted PEDOT in polyacrylamide hydrogel for high performance supercapacitors and self-powered sensing system. (5th October 2022) - Chen, Chen; Li, Yueqin; Qian, Changhao; Liu, Xiaohui; Yang, Yong; Han, Lin; Han, Qingshan
Graphical abstract: Highlights: Multifunctional conductive CMC-PEDOT/PAAM hydrogels have been prepared and optimized. Flexible supercapacitors based on CMC-PEDOT/PAAM film exhibit enhanced electrochemical performances. The all-in-gel supercapacitor can be operated over a wide temperature range. The CMC-PEDOT/PAAM hydrogels can be developed into a self-powered sensing system for human-motion detection. Abstract: In this paper, we study the role of carboxymethyl cellulose (CMC) as a template for helping poly(3, 4-ethylenedioxythiophene) (PEDOT) uniformly disperse into polyacrylamide (PAAM) hydrogel scaffold. The presence of a large amount of hydrogen bonds and chain entanglements enabled excellent mechanical properties with great stretchability and resilience. With the optimum mass loading of PEDOT (9.75 mg/cm 2 ), a sandwiched configuration of flexible supercapacitor based on the CMC-PEDOT/PAAM hydrogel can deliver the highest specific capacitance of 269 mF/cm 2, a maximum energy density of 23.93 μWh/cm 2 at a power density of 400 μW/cm 2 and remained 16.18 μWh/cm 2 at a power density of 3200 μW/cm 2, as well as enhanced cycle stability with 88% retention after 5000 cycles. In addition, such device can withstand severely bending and compressing deformations and properly operate at extreme temperatures (−40 ∼ 90 °C) with excellent capacitance property. What's more, the excellent conductivity of the CMC-PEDOT/PAAM hydrogel contributed to outstanding strain sensing performances. When the supercapacitor was used to power the hydrogel strain sensor, the obtained self-powered sensing system is capable of monitoring physiological signals accurately. The multifunctional performance of the CMC-PEDOT/PAAM hydrogel could be potentially used in flexible electronic devices.